The Position of “Power” when Engaging Marginalised Youth - Moroke, Mapule Sheena; Graham, Tanya Monique (PINS-Psychology in Society, 2022)
Qualitative data analysis underlines the importance of the researcher’s reflexivity, which involves the researcher’s own values, experiences, interests, beliefs, and social identities that may have shaped the research and the data analysis process. The identity of the researcher influences his or her choice of a particular research topic. Thus researchers should reflect on how past personal experiences influence them to choose certain research topics, and an understanding of the self within the research context helps in being critical of his or her work. This article examines the experience of power as researchers, as engaged in a qualitative study of marginalised youth from Orlando West, Soweto, on the growing phenomena of train surfing. The navigation of race, gender and perceived class shifted our understandings and perceptions of how identity is constructed by adolescents and allowed for a platform for alternative youth voices to be heard. These voices spoke of how issues of race, gender and class may predispose them to certain difficulties, but there was a simultaneous acceptance and rejection of stereotypical outcomes associated with their age, gender, and race. The article illustrates how qualitative methods of research can be used as a tool of “social change research”, as experienced by the researchers through personal reflection.